Can the Palliative Care Outcome Scale be used to measure the positive impact of a hospital based palliative care liaison team?. Issue Volume 4: Issue (2014)Supplement 1 (1st March 2014) - Whitehurst, Jane; Michaels, Katherine; Montacute, Nicola; Williams, Sue; Ward, Brenda; Gillett, Janet
Abstract : Background: The Palliative Care Outcome Scale (POS) is a holistic, validated, Patient Reported Outcome Measure (PROM). PROMs can enable evaluation of patient care, helping to improve service quality. Aims: To assess POS as a tool for patient assessment and clinical audit in a nurse-led hospital liaison palliative care team (HPCT). Methods: We used POS and POS-S (symptoms) at initial, weekly and last consultations in 30 patients and evaluated the HPCT experience of this. We used the following Minimal Clinically Important Difference in scores to determine PCT effectiveness 80% percent achieving a one-point reduction in pain score Statistically significant reductions in grouped POS and POS-S scores (Wilcoxon signed rank test) Results: The HPCT saw 57 patients to collect 30 patients' data. (23 clinically unsuitable, 4 missed). Follow-up questionnaires were available in 19 patients for POS, 15 for POS-S (7 patients seen once, 1 data set destroyed, remainder missed). A one-point reduction in pain score occurred in 74% patients (14 out of 19 with follow-up POS data). Both POS and POS-S median scores improved. POS median score: initial consultation 17, last consultation 6 (p=0.002) POS-S median score: initial consultation 17, last consultation 8.5 (p=0.04). ▸ The HPCT felt that POS was useful to: ▸ Establish the patient's agenda ▸ Enable early discussion of psychosocial concerns ▸ Reduce the risk of missing significant needs Concerns were: ▸ The staff time required to complete POS ▸ That patients found repeated questionnaires burdensome That POS data may underestimate HPCT effectiveness as sometimes advice was disregarded and patients were discharged before a final assessment Conclusions: The HPCT significantly improved patient well-being. However, repeat use of POS was burdensome and low inclusion and follow-up rates suggest POS is not a suitable audit tool to measure our HPCT effectiveness at this time. Using POS and POS-S at the initial consultation usefully established the patients' baseline status and needs. The HPCT will continue to use it in this manner.